Identificação e distribuição geográfica dos curculionídeos-das-raízes da soja no Rio Grande do Sul - Bigolin, Mauricio (2013)
The occurrence of root weevils in the systems of production of soybeans has shown a significant increase in the southern region of the country in the last decade, however, there is little information about the species, its distribution and damage of this group of insects in soybeans. This study aimed to identify the species of root weevils associated with soybean, to study geographical distribution and develop an identification key of species of adult root weevils in Rio Grande do Sul. The survey of the occurrence and geographical distribution of root weevils was conducted in commercial soybean plantations of 55 municipalities of Rio Grande do Sul, during the agricultural harvest 2011/12. In each location / municipality, 15 points per farming were sampled, using the sampling method of insect net. The collected samples were placed in plastic containers containing 70% alcohol and sent to the laboratory, for later identification, quantification and assembly of entomological collection. After the identification, the occurrence of 12 species of weevils roots associated with soybean in RS was recorded, belonging to four genera. The genus Naupactus had the highest number of insects, totaling 9 species. Naupactus cervinus was the species that occurred in more locations, being found in 22 municipalities in the RS, distributed in all regions of leguminous production in the state. The species of root weevils presented in the key of identification are: Aramigus conirostris (Hustache), Atrichonotus sordidus (Hustache), Naupactus alternevittattus Hustache, Naupactus ambiguus Boheman, Naupactus cervinus Boheman, Naupactus cinerosus Boheman, Naupactus leucoloma Boheman, Naupactus minor (Buchanan), Naupactus peregrinus Buchanan, Naupactus purpureoviolaceus Hustache, Naupactus tremolerasi Hustache and Pantomorus viridisquamosus (Boheman).